2018
DOI: 10.1186/s13023-018-0846-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and healthcare burden of pulmonary alveolar proteinosis

Abstract: Pulmonary alveolar proteinosis (PAP) is a rare syndrome of alveolar surfactant accumulation, resulting hypoxemic respiratory failure, and increased infection risk. Despite advances in our understanding of disease pathogenesis and the availability of improved diagnostics, the epidemiology and healthcare burden of PAP remain poorly defined. To determine the prevalence, and healthcare utilization and costs associated with PAP, we interrogated a large health insurance claims database containing comprehensive data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 9 publications
3
53
0
1
Order By: Relevance
“…Our results showed a low prevalence of PAP in Korea (4.44 per 10 6 people from 2010 to 2016), similar to that in Japan [4,11]. Inoue Y. et al, using national cohort data from 9 primary clinical research centres in Japan, reported that the prevalence of autoimmune PAP was 6.2 per 10 6 population between 1999 and 2006 [4].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our results showed a low prevalence of PAP in Korea (4.44 per 10 6 people from 2010 to 2016), similar to that in Japan [4,11]. Inoue Y. et al, using national cohort data from 9 primary clinical research centres in Japan, reported that the prevalence of autoimmune PAP was 6.2 per 10 6 population between 1999 and 2006 [4].…”
Section: Discussionsupporting
confidence: 81%
“…This could explain the late diagnostic age of PAP observed in our current study. Recent prevalence of PAP in United States between 2008 and 2012 peaked at over 75 years followed by the aged 65-74 years also supports the global aging of PAP patients [11].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The prevalence of PAP in the United States determined from claims database of 15 million patients was estimated at 6.87 per million. 55 A recent report from Japan which employed a Poisson distribution to the number of cases diagnosed annually in a specific region estimated that the incidence and prevalence of autoimmune PAP is 1.65 and 26.6 per million, respectively, suggesting the prior numbers were underestimates. Autoimmune PAP accounts for approximately 90% of the cases 4,55 and the average age of diagnosis is between 39 and 43 years, with a slight male predominance.…”
Section: Clinical Features Of Pap Epidemiologymentioning
confidence: 99%